2012
DOI: 10.1007/s10867-012-9282-8
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies in the motion dynamics of long-flagella mutants of Chlamydomonas reinhardtii

Abstract: Chlamydomonas reinhardtii has long been used as a model organism in studies of cell motility and flagellar dynamics. The motility of the well-conserved '9+2' axoneme in its flagella remains a subject of immense curiosity. Using high-speed videography and morphological analyses, we have characterized long-flagella mutants (lf1, lf2-1, lf2-5, lf3-2, and lf4) of C. reinhardtii for biophysical parameters such as swimming velocities, waveforms, beat frequencies, and swimming trajectories. These mutants are aberrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
4
16
0
Order By: Relevance
“…6A). Those results are compatible with the work of Khona, et al, on long-cilia mutants (44). In the prior study four lf mutants were analyzed and displayed a reduced beat frequency (by 8-16%) as well as a reduced swimming velocity (by 26-57%) for cilia length >18 µm.…”
Section: Limitationssupporting
confidence: 90%
See 1 more Smart Citation
“…6A). Those results are compatible with the work of Khona, et al, on long-cilia mutants (44). In the prior study four lf mutants were analyzed and displayed a reduced beat frequency (by 8-16%) as well as a reduced swimming velocity (by 26-57%) for cilia length >18 µm.…”
Section: Limitationssupporting
confidence: 90%
“…Long-cilia mutant. We did not study cilia behavior in extremely long cilia such as those of lf mutants (44,67,68). In the current study, using wild-type cells we observed that rotation rate and forces applied by the cilium increased with length.…”
Section: Limitationsmentioning
confidence: 99%
“…The wild type (cc124) and mutant strains deficient in the RS ( pf14) and CP ( pf14 , pf15 , pf16 , pf18 , pf19, and pf20) and cc620, cc621 were procured from Chlamydomonas Resource Center (University of Minnesota). All cells were grown in liquid TAP medium with continuous light under shaking conditions at 25 °C [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown and maintained by periodic transfers in Tris Acetate Phosphate (TAP; pH 7) medium as mentioned by Khona et al. . For all experiments, ~1 × 10 8 cells · mL −1 were exposed to different concentrations of menadione (5, 10, 50, 100, and 200 μM).…”
Section: Methodsmentioning
confidence: 99%